The pH Effect on the Growth of Hexagonal and Monoclinic Hydroxyapatite Synthesized by the Hydrothermal Method. (8th December 2020) - López-Ortiz, S.; Mendoza-Anaya, D.; Sánchez-Campos, D.; Fernandez-García, M. E.; Salinas-Rodríguez, E.; Reyes-Valderrama, M. I.; Rodríguez-Lugo, V.
Abstract : Summary . In the present work, a study of H + effects on the microstructure and morphology of hydroxyapatite synthesized by the hydrothermal method is reported. The synthesis was realized with pH values of 10, 9.6, 9, 8, and 7. To know the particle size distribution, growth habit, chemical composition, and crystalline phases present, SEM-EDS, XRD, AFM, and FTIR spectroscopy techniques were used and completed with Rietveld analysis. The obtained results showed an important effect of H + on the morphological and crystallographic characteristics of the hydroxyapatite, demonstrating that the shape and nanoparticle size, as well as the number of crystalline phases, can change depending on the pH during the synthesis. It was observed that there is an increase in the formation of the monoclinic phase and a decrease of the hexagonal phase when the pH value diminishes from 9.6 to 7. The crystallite size also decreases from 46.69 to 19.56 nm. An explanation of the role of pH on the final characteristics of the hydroxyapatite was related to the amount of H + and OH - ions, and it was included in this work.